Assistance in Designing Brand Guidelines to Develop a Professional Identity for Young Generation - B. Azhar, Iman Saladin; Sari, Winda Kurnia; Exaudi, Kemahyanto; Prasetyo, Aditya Putra Perdana; Putra, Pacu; Firnando, Ricy (Institut Teknologi Nasional, Bandung, 2026)
This community service programme aims to support the youth participants of Rumah Cahaya Indonesia (RCI) Palembang in designing a comprehensive Brand Guideline to strengthen their professional identity. The main problem identified is the inconsistency of visual identity and the limited understanding of branding principles among the participants. To address this issue, the programme implements workshops and technical mentoring sessions focusing on fundamental branding concepts, the structure and components of a Brand Guideline, and the importance of maintaining consistent visual communication. The activities include preparation, development of learning materials, workshop implementation, hands-on practice, and evaluation. Participants are trained to use Adobe Illustrator and Adobe After Effects to produce visual and motion-based brand assets. The programme received positive feedback, indicating an improvement in participants’ understanding and skills in branding. The results show that this initiative contributes to enhancing digital creative literacy and supports young people in developing a more structured and professional brand identity.